2005
DOI: 10.1136/jech.2004.023374
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dislike of school on risk of teenage pregnancy: testing of hypotheses using longitudinal data from a randomised trial of sex education

Abstract: Study objective: To examine whether attitude to school is associated with subsequent risk of teenage pregnancy. To test two hypotheses that attitude to school is linked to pregnancy via pathways involving young people having ''alternative'' expectations or deficits in sexual health knowledge and confidence. Design: Analysis of longitudinal data arising from a trial of sex education. Examination of associations between attitude to school and protected first sex, unprotected first sex, unprotected and protected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 11 publications
(7 reference statements)
5
63
0
Order By: Relevance
“…School activities are not likely to reach those persistently absent from school, young people who have left school early, or young offenders. They may not necessarily appeal to young people who are disaffected by school and the education system in general, 173 although the influence of credible peer educators may help to overcome this. As explained earlier, school-based interventions were prioritised for our systematic review because, in consultation with stakeholders, it was considered that they were likely to reach the greatest number of young people.…”
Section: The Wider Evidence Basementioning
confidence: 99%
“…School activities are not likely to reach those persistently absent from school, young people who have left school early, or young offenders. They may not necessarily appeal to young people who are disaffected by school and the education system in general, 173 although the influence of credible peer educators may help to overcome this. As explained earlier, school-based interventions were prioritised for our systematic review because, in consultation with stakeholders, it was considered that they were likely to reach the greatest number of young people.…”
Section: The Wider Evidence Basementioning
confidence: 99%
“…[24][25][26] Some research has demonstrated that poor parentadolescent communication and a lack of parental supervision are associated with potentially risky sexual behavior outcomes in diverse groups. [27][28][29] We hypothesized that increased family and school connectedness would be negatively associated with our behavioral outcomes.…”
Section: Factors Associated With the Sexual Behavior Of Canadian Abormentioning
confidence: 99%
“…The association between school failure, lack of interest in school or lack of academic and professional future plans and teenage pregnancy has already been studied. 14 As for contraception, the main contraceptive methods used prior to a pregnancy carried until delivery were oral combined contraceptives and male condoms. These data match the findings of other authors, according to which most adolescents use contraceptive methods which are more user dependent.…”
Section: Discussionmentioning
confidence: 99%